Prevalence of High-Risk HPV Genotypes (16, 18, 31, and 45) and Cervical Cytological Abnormalities among Women in Eastern India: A Cross-Sectional Pilot Study from a Screening Cohort - Turuk, Jyotirmayee; Mishra, Debadutta; Biswas, Sutapa; Palo, Seetu; Mondal, Deepa; Mishra, Bharadwaj (Annals of Pathology and Laboratory Medicine, 2025)
Background: Persistent infection with high-risk HPV (HR-HPV) types is a major risk factor for cervical cancer. Regional data on HPV prevalence is essential for effective screening and vaccination strategies. Materials and Methods: A cross-sectional study was conducted among women attending cervical cancer screening camps in Bhubaneswar. Paired cervical and urine samples were collected. DNA was extracted and analyzed for HR-HPV types 16, 18, 31, and 45 using molecular techniques. Cervical smears were evaluated according to the Bethesda System 2014 for reporting cervical cytology. Results: Of 125 women included, HR-HPV DNA was detected in 3 (2.4%) cases [HPV16/31, HPV18/45, and HPV16]. All HPV-positive cases had a parity of two. Concordance between cervical and urine samples was 100%. Cytology showed inflammatory changes in most cases (72.8%), with only two cases (1.6%) reported as atypical squamous cells of undetermined significance (ASCUS), one of which was also HPV16 positive. Conclusion: The prevalence of HR-HPV in this cohort was low. The high concordance between urine and cervical samples suggests urine as a viable non-invasive option for HPV detection. These findings support the integration of urine-based screening and call for broader HPV genotyping and larger-scale studies to better inform regional public health strategies.